Makna Filosofis Uborampe Pasang Tarub dan Siraman pada Upacara Pernikahan Adat Jawa di Kradenan Jawa Tengah - Nuryuana Dwi Wulandari; Nugraha Nugraha; Anggar Kaswati (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
Pairs of tarub and siraman are a series of traditional Javanese wedding ceremonies. This study aims to find out: 1) General description of Kradenan village community; 2) carrying out the procession of pairs of tarub and siraman in Kradenan village; 3) uborampe procession of pairs of tarub and siraman in Kradenan village and 4) philosophical meaning of uborampe procession of pairs of tarub and siraman in Kradenan village. In this study, the focus was on the procession of installing tarub and siraman with a case study of the Central Java kradenan. This study used qualitative research methods. The results of this study 1) the people of Kradenan village are mostly Muslim with a firm adherence to culture; 2) Installation of Tarub as a sign that there will be a wedding ceremony, while for Siraman in Kradenan Village. it is carried out after the installation of Tarub; 3) each uborampe used in the procession has a philosophical meaning; 4) the entire uborampe used in the procession of pairs of tarub and siraman has the meaning of prayer so that the household remains harmonious, protected from harm and avoided divorce.